Baptism, Eucharist, and the earliest Jesus-groups – from the perspective of alternate states of consciousness - Van Aarde, A.G. (Andries G.) (University of Pretoria, 2013)
Thesis (DD (New Testament Studies))--University of Pretoria, 2007.